Arterial stiffness evaluation by pulse wave velocity in hypertension and diabetes mellitus subjects (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Â Background: Arterial stiffness is an independent predictor for vascular diseases. Carotid-femoral pulse wave velocity (CFPWV) is a reliable index of arterial stiffness. In the present study, we investigated the possible risk factors involving CFPWV in hypertension and diabetes mellitus (DM) subjects.Methods: 425 subjects (M/F 168/257) from Shougang Corporation Examination Center were divided into four groups: healthy group (n=185), hypertension group (n=135), DM group (n=32), hypertension with DM group (n=73). CFPWV was measured by Complior apparatus.Results: Our results showed that CFPWV was significantly higher in hypertension subjects with DM than in healthy and hypertension group, respectively (12.00+2.57 vs 10.12+2.28 m/s; 12.00+2.57 vs 10.78+2.07 m/s, both p